DEVELOPING CREATIVE THINKING IN FUTURE TEACHERS - Jumayeva Mehribo (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
The article discusses effective ways of developing the creative abilities of future pedagogues in the modern educational process. It highlights the importance of creativity in professional pedagogical activity and analyzes innovative approaches, interactive teaching methods, and pedagogical technologies used in the development of students’ creative thinking skills. The study also emphasizes the role of independent learning, problem-based education, and collaborative activities in enhancing creativity. In addition, the article considers the pedagogical conditions necessary for forming creative competence and increasing the intellectual and innovative potential of future teachers.